The landscape of alternative polyadenylation in single cells of the developing mouse embryo - Vikram Agarwal (Nature Portfolio, 2021)
Alternative polyadenylation regulates localization, half-life and translation of mRNA isoforms. Here the authors investigate alternative polyadenylation using single cell RNA sequencing data from mouse embryos and identify 3’-UTR isoforms that are regulated across cell types and developmental time.